Isothermal and Kinetic Evaluation of Adsorption Fish Farm Effluents by Nanocomposites (Chitosan and Activated Carbon) - Hassan Rezaei; Saeedeh Rastegar; Seyyed Aliakbar Hedayati; Yousef Dadban Shahamat; Omid Sedaghat (Journal of Advances in Environmental Health Research, 2021)
Background: In wastewater treatment, removal of phosphate and ammonia is of great importance. Chitosan is a copolymer, which can be applied in low-cost adsorption. Thus, in this study, chitosan and activated carbon nanocomposite adsorbents were prepared to remove organic pollutants from the fish farm effluents.Methods: This study was performed at different physicochemical conditions of pH (5-8), effluent dose (25-100 mg/L), and contact time (15-90 min) minutes. Adsorption isotherm studies were analyzed using Freundlich, Langmuir models, and adsorption kinetics studies.Results: The Langmuir and Freundlich isotherms for nitrite (R2=0.9076, R2=0.5911), phosphate (R2=0.9307, R2=0.5755), and ammonia (R2=0.7288 and R2=0.7549) were respectively obtained. According to the results, the data of nitrite and phosphate pollutants were more consistent with the Langmuir model, but the data of ammonia pollutants were more consistent with the Freundlich. The best optimal adsorption occurred at a pH=7. Elevation of the initial concentration of the pollutant led to the depletion of the removal functions. With increasing the contact time, adsorption efficiency increased.Conclusion: Finally, with respect to the obtained elimination percentage (R=99.98%), chitosan and activated carbon nanocomposites have a high ability to remove organic pollutants.